Perancangan Prototype Sistem Informasi PPDB Berbasis Web pada PAUD Bu Piah - Bagus Ponco Wibowo; Dian Shinta Mareta; Rizqi Andhika Pratama (CV. Multi Kreasi Media, 2026)
The development of information technology has encouraged digital transformation in various sectors, including education. One administrative activity that requires effective management is New Student Admission (PPDB). PAUD Bu Piah still carries out the PPDB process manually, causing problems such as limited information dissemination, inefficient registration processes, and the risk of data loss. This study aims to design a web-based PPDB Information System prototype that can assist registration and student data management effectively. The research method used is Prototype, consisting of requirement gathering, prototype development, evaluation, and refinement. The results indicate that the designed system provides school information services, online registration, document uploads, applicant data management, and an admin dashboard. The proposed system is expected to improve administrative services and support educational digitalization.